Prevalensi Indikasi Perawatan Endodontik di URJT RSUPN Dr. Cipto Mangunkusumo Tahun 2024 - Larasputri, Indira; Indriutami, Ratna; Sandini, Ayu; Ningrum, Yuli Puspa; Novitasara, Ivit (Al Makki Publisher, 2025)
Pulp disease is a common dental health problem requiring endodontic treatment. Prevalence data is crucial for developing standard operating procedures and healthcare service planning. To determine the prevalence of endodontic treatment indications among patients visiting the Integrated Outpatient Unit of RSUPN dr. Cipto Mangunkusumo Jakarta in 2024. A descriptive cross-sectional study was conducted on 100 patients aged at least 18 years using quota sampling technique. Data were collected through clinical examinations including anamnesis, visual examination, percussion tests, and cold tests. Of 100 examined patients, 31% required endodontic treatment, with 25% undergoing root canal treatment and 6% receiving pulp capping. Gender distribution showed 60% female and 40% male patients. The 55-65 years age group had the highest prevalence for root canal treatment. Molars were the most frequently treated teeth (64.5%), followed by premolars (25.8%) and anterior teeth (9.7%). The prevalence of endodontic treatment indications at the Integrated Outpatient Unit of RSUPN dr. Cipto Mangunkusumo in 2024 was 31%, with the majority being root canal treatments in middle-aged to elderly patients.